Farm Productivity and Market Structure. Evidence From Cotton Reforms in Zambia - Irene Brambilla; Guido G. Porto (Yale University, Economic Growth Center, 2005)
This paper investigates the impacts of cotton marketing reforms on farm productivity, a key element for poverty alleviation, in rural Zambia. The reforms comprised the elimination of the Zambian cotton marketing board that was in place since 1977. Following liberalization, the sector adopted an outgrower scheme, whereby firms provided extension services to farmers and sold inputs on loans that were repaid at the time of harvest. There are two distinctive phases of the reforms: a failure of the outgrower scheme, and a subsequent period of success of the scheme. Our findings indicate that the reforms led to interesting dynamics in cotton farming. During the phase of failure, farmers were pushed back into subsistence and productivity in cotton declined. With the improvement of the outgrower scheme of later years, farmers devoted larger shares of land to cash crops, and farm productivity significantly increased.
Keywords: O12; O13; Q12; Q18; 330; cotton marketing reforms; farm productivity; Produktivität; Landwirtschaft; Agrarverwaltung; Deregulierung; Schätzung; Sambia